Wet, wetter, wettest: Amazon rainforest responsiveness to short-term drought - Gallup, Sarah, author; Baker, Ian, author; Denning, A. Scott, author; Cheeseman, Michael, author; Haynes, Katherine, author (Colorado State University. Libraries, 2017)
The Amazonian rainforest’s massive gas exchanges with the atmosphere strongly affect CO2 concentrations globally. Dry periods in the Amazon are expected to become more common and could hinder vegetation. We compare a proxy measure of photosynthetic rate, solar-induced fluorescence (SIF) from the Orbiting Carbon Observatory 2 (OCO-2) satellite, to rainfall in the previous 30 days. In the climatologically wettest regions, photosynthesis barely responded or even increased in response to short-term drying. In rainforest areas with longer dry seasons, photosynthesis weakly declined after reduced rain. The finding is consistent with and more precise than earlier studies, and offers a metric for evaluating photosynthesis projections for the Amazon.
109 - Sarah M Gallup
Wet, wetter, wettest: Amazonian rainforest responsiveness to recent precipitation
Displayed at Colorado State University's Grad Student Showcase, 2017.
Keywords: OCO-2; chlorophyll influorescence; SIF; gross primary productivity; Amazon; drought